Diagnostic and prognostic potential of the use of ultrasound and three-dimensional endo-visualization in women with pelvic varicose veins - Aleksandr I Gus; Dmitrii A Stupin; Andrei A Semendiaev; Mariia A Cherepanova; Natalia V Akudovich (IP Berlin A.V., 2019)
Aim. To study the diagnostic and prognostic potential of the complex use of ultrasound and 3D laparoscopy in women with pelvic varicose veins (PVV). Outcomes and methods. The study included 100 women who were divided into two groups: the main group (39 patients with various severity PVV) and the control group (61 women with no venous system disorders). All patients had a complete clinical examination with the selection of pairs that had the most significant factors for the disease prognosis: average age over 35 years, history of varicose veins, pain in the lower abdomen, dysmenorrhea and dyspareunia. Examination of the small pelvis venous system included duplex angioscanning and retrograde endoscopic functional test controlled by the three-dimensional image. Multivariate analysis (logistic regression) was used to identify normative phlebological parameters. Results. Predictors of early PVV are the following rations: Vmax in the cava-ovarian segment / Vmax in the right ovary portal ≥ 8.3 and Vmax in the reno-ovarian segment /Vmax in the left ovarian portal ≥ 8. The severity of PVV is determined by a progression of alterations in hemodynamic parameters in the main ovarian veins and a spreading venous congestion in the small pelvis plexuses. Conclusions. Criteria of small pelvis phlebohemodynamics make it possible to predict a development of PVV and a severity of the pathological process. Ovarian varicose veins are characteristic of early PVV and venous plethora of all pelvis venous plexuses is characteristic of late PVV.